PENGARUH PENGENCERAN DAN PENGADUKAN PADA PRODUKSI BIOGAS DARI LIMBAH RUMAH MAKAN DENGAN MENGGUNAKAN STARTER EKSTRAK RUMEN SAPI - Eka Triakuntini; Sudarno Sudarno; Endro Sutrisno (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
With the increasing amount of human needs for energy, a new energy source is needed to replace the use of fossil fuel which existence becoming rare. One alternative energy than can be used is biogas. Biogas is a gas formed from organic matter decomposition in an anaerob condition. Biogas can be made from materials easily found in the environment, such as restaurant waste that has high organic components. To improve biogas production, there are several treatments that can be done, such as dilution and mixing. This study uses 10 digesters, each of it filled with 4 kg restaurant waste and 1.5 L cow rumen, with the addition of water varies as follows: 6000 ml, 4000 ml, 2600 ml, 1500 ml and 670 ml. The first five digesters were being mixed while the other five were not. The observation runs for 22 days. Result shown that in both digesters with water content as much as 6000 ml, with mixing or not, are the ones that produce the most gas. First digester produces 1032.02 ml gas while sixth digester produces 1196.99 ml gas. To compare the effect of mixing, gas production on digesters with no mixing produce more gas than the one that are being mixed.